(untitled) (UNIZIK Journal of Marketing, 2025)
This study examined the effect of market orientation strategy on marketing performance of telecommunication organizations in Enugu state Nigeria. The study was quantitative in nature and adopted correlational research design. The population of the study was staff of telecommunications organizations in Enugu state, Nigeria. The Sample size of the study was 384 staff of telecommunications organizations in Enugu state selected using purposive sampling. The instrument of data collection was a structured questionnaire. The structured questionnaire was validated using expert opinion while Cronbach alpha was used to test the reliability whereupon all the variables surpassed the accepted and recommended 6.0. Pearson product moment correlation coefficient and multiple regression analysis were used to analyze the data collected with the aid of Statistical Package for Social Sciences (SPSS. version 26.0). The results showed that all the five market orientation strategies understudy including: customers’ orientation, competitors’ orientation, inter-functional coordination, market intelligence generation and responsiveness have significant effect on marketing performance of telecommunications organizations in Enugu state Nigeria. The implication of this is that management of telecommunications organizations in Enugu state Nigeria should effectively coordinate all elements of market orientation for effective customer services delivery to meet changes in the market and improve their marketing performance.